A farewell to Gabo and Mercedes a son's memoir of Gabriel García Márquez and Mercedes Barcha - García, Rodrigo 1959- (HarperVia, an imprint of HarperCollinsPublishers, 2021)
"In March 2014, Gabriel García Márquez, one of the most internationally beloved writers of the 20th century, came down with a cold. He was almost 87 years old, and battling dementia. 'I don't think we'll get out of this one,' Mercedes Barcha, his wife of over fifty years, told Rodrigo, their son. As reality begins to sink in, Rodrigo asks himself, 'Is this how the end begins?' Instead of waiting for an answer, Rodrigo starts to write about the beginning of the end. The resulting pages became A Farewell to Gabo and Mercedes --
Keywords: García Márquez, Gabriel / 1927-2014 / Family; Barcha, Mercedes; García, Rodrigo / 1959-; Novelists, Colombian / Biography; García Márquez, Gabriel / 1927-2014; Families; Novelists, Colombian; Biography; Biographies